2008
DOI: 10.1021/jp803254d
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Characterization of Structural Isomers of Naphthalene: (E)- and (Z)-Phenylvinylacetylene

Abstract: Near-pure samples of (E)-phenylvinylacetylene ((E)-PVA) and (Z)-phenylvinylacetylene ((Z)-PVA) were synthesized, and their ultraviolet spectroscopy was studied under jet-cooled conditions. The fluorescence excitation and UV-UV holeburning (UVHB) spectra of both isomers were recorded. The S0-S1 origin of (E)-PVA occurs at 33,578 cm(-1), whereas that for (Z)-PVA occurs at 33,838 cm(-1), 260 cm(-1) above that for (E)-PVA. The present study focuses primary attention on the vibronic spectroscopy of (E)-PVA. Single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 69 publications
3
28
0
Order By: Relevance
“…28,29 Recent combined computational and experimental investigations showed that in order to achieve quantitative assignments for single vibronic level fluorescence spectroscopy in phenylvinylacetylene, Duschinsky rotation effects are imperial, which posed computational challenges for quantum chemistry. 37,38 Under the Franck-Condon approximation, the IC rate can be expressed as…”
Section: Methodology and Computational Schemesmentioning
confidence: 99%
“…28,29 Recent combined computational and experimental investigations showed that in order to achieve quantitative assignments for single vibronic level fluorescence spectroscopy in phenylvinylacetylene, Duschinsky rotation effects are imperial, which posed computational challenges for quantum chemistry. 37,38 Under the Franck-Condon approximation, the IC rate can be expressed as…”
Section: Methodology and Computational Schemesmentioning
confidence: 99%
“…46 This is consistent with what is observed in the corresponding series of C 4 phenyl derivatives, where trans-PVA and PDA are 263 and 2916 cm À1 blue of PBD. 62,64 All three diphenyl molecules in the series undergo rapid internal conversion or intersystem crossing that result in a loss of fluorescence within a few hundred wavenumbers of their origins, though the exact nature of the processes has not been fully determined, and may differ within the series. One of the most notable differences between DPDA, DPVA, and DPBD is the breadth of their transitions in the near-ultraviolet.…”
Section: Diphenyl Comparisonmentioning
confidence: 99%
“…Our recent studies of the spectroscopy and isomerization of trans-and cis-phenylvinylacetylene (PVA) have led to the conclusion that the vinylacetylene substituent produces vibronic spectra similar in many ways to those of styrene and stilbene. 41,42 A reversal of the order of substitution to make 1-phenyl-1-butyn-3-ene (PAV) produces a vibronic spectrum with characteristics similar to those of phenylacetylene. 43 Capping the end of either PVA or PAV with a second phenyl ring produces diphenylvinylacetylene (DPVA).…”
Section: Introductionmentioning
confidence: 99%
“…The cis and trans isomers of 4-phenyl-1-butene-3-yne (phenylvinylacetylene, labeled hereafter as Z-PVA and E-PVA) are one pair of C 10 H 8 isomers recently explored in some detail. 7 Photoisomerization of each of these isomers has also been studied using the newly developed method of ultraviolet population transfer spectroscopy. 8 Here, we report on the ultraviolet spectroscopy of a close analog of PVA in which the order of the ethynyl and vinyl groups relative to the phenyl ring are swapped, 1-phenyl-1-butyne-3-ene, labeled as PAV in order to highlight the re-ordering of the conjugated substituents.…”
Section: Introductionmentioning
confidence: 99%